2003
DOI: 10.1016/s0028-3932(02)00175-6
|View full text |Cite
|
Sign up to set email alerts
|

Theory of mind and psychopathy: can psychopathic individuals read the ‘language of the eyes’?

Abstract: There have been suggestions that Theory of Mind (ToM) impairment might lead to aggressive behaviour and psychopathy. Psychopathic and matched non-psychopathic individuals, as defined by the Hare Psychopathy Checklist [The Hare Psychopath Checklist-Revised, 1991] completed the 'Reading the Mind in the Eyes' ToM Test [Journal of Child Psychology and Psychiatry, 1997;38:813]. This test requires the self-paced identification of mental states from photographs of the eye region alone. Results indicated that the ps… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
190
5
11

Year Published

2004
2004
2020
2020

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 310 publications
(223 citation statements)
references
References 12 publications
15
190
5
11
Order By: Relevance
“…Because lack of empathy and callousness are typical traits among psychopaths, our findings can be interpreted as further empirical evidence for the joint role of testosterone and cortisol in psychopathy. From this perspective, the lack of a significant effect of steroid hormones on RMET, a measure of cognitive empathy, is not surprising, as previous reports showed that psychopaths do not differ from controls in their RMET performance (Richell et al 2003) and no negative correlation exists between total RMET and selfreported psychopathic traits in non-clinical populations (Sandvik et al 2014), which, on the contrary, negatively predict IRI scores (Zágon and Jackson 1994). Further, it is possible that the RMET, which was mainly designed for individuals with mild deficits in social cognition (Baron-Cohen et al 2001) may not be very sensitive to individual variation within the normal range (e.g., see Voracek andDressler 2006, but see Van Honk et al 2011 4 ).…”
Section: Discussionmentioning
confidence: 88%
“…Because lack of empathy and callousness are typical traits among psychopaths, our findings can be interpreted as further empirical evidence for the joint role of testosterone and cortisol in psychopathy. From this perspective, the lack of a significant effect of steroid hormones on RMET, a measure of cognitive empathy, is not surprising, as previous reports showed that psychopaths do not differ from controls in their RMET performance (Richell et al 2003) and no negative correlation exists between total RMET and selfreported psychopathic traits in non-clinical populations (Sandvik et al 2014), which, on the contrary, negatively predict IRI scores (Zágon and Jackson 1994). Further, it is possible that the RMET, which was mainly designed for individuals with mild deficits in social cognition (Baron-Cohen et al 2001) may not be very sensitive to individual variation within the normal range (e.g., see Voracek andDressler 2006, but see Van Honk et al 2011 4 ).…”
Section: Discussionmentioning
confidence: 88%
“…To assess individual variation in a behavioral measure of empathic accuracy, participants completed the ''Reading the Mind in the Eyes'' Test (RMET), which tests for the empathic ability to infer the emotional states of others (11,(26)(27)(28)(29). Previous studies have documented that impaired performance on the RMET predicts higher scores on a measure of autistic traits in both clinical and control groups (27,29).…”
Section: Resultsmentioning
confidence: 99%
“…Although theory of mind skill disorders were found in certain studies, no difference was found in other studies compared to the healthy conAnatolian Journal of Psychiatry 2019; 20(1):5-12 trols. 36,37 Richell et al 38 reported that the theory of mind skills were not affected in case of personality disorders.…”
Section: Discussionmentioning
confidence: 99%